Tecnología en almacenes y centros de distribución - Castillo Barrenechea, Deborah Andrea (2021)
The technology applied in warehouses is increasingly diverse and undoubtedly offer many benefits both to increase the productivity of the company and to be more responsive to customer needs. This technology are systems such as software, devices or mechanical equipment that allow better visibility of the stored products and increase the efficiency in the mobilization of the products. These systems are more used in industries with a large volume of products since it allows better control of the location of these, of the incoming and outgoing inventory and providing benefits in productivity and speed of attention and collection of customer orders. Authors such as Ribeiro, Silva, & Benvenuto (2006) show in their studies that the application of these systems, such as the WMS, allows reducing costs, delays in deliveries and an increase in the productivity of logistics operations. The application of these systems requires a great investment, so the best alternative must be evaluated due to the implementation of these depends on the size and type of warehouse that is owned.